DIAGNOSTIC EXAMINATION METHODS IN WOMEN WITH BREAST CANCER (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Every year, approximately 1.38 million women are diagnosed with breast cancer, and more than 500,000 die from the disease (IARC, Globocan, 2012). Breast cancer is currently the most common malignant disease among women in both developed and developing countries worldwide. While prevention can reduce some risk factors, such strategies do not prevent the majority of breast cancer cases in low- and middle-income countries, where the disease is often diagnosed at very late stages. The incidence rate is widespread globally, with age-standardized rates of 99.4 per 100,000 people in North America. In Eastern Europe, South America, South Africa, and Western Asia, the incidence is relatively low, but a recent increase has been observed.